A comparative analysis of survival outcomes and adverse effects between preoperative brachytherapy with radical surgery and concurrent chemoradiotherapy in patients with locally advanced cervical cancer - Niu, Yuna; Du, Chengchao; Zhou, Yeqin; Zhang, Miao; Guo, Qi; Zhou, Honggui (Frontiers in Oncology, 2025)
BackgroundTo compare the long-term efficacy and adverse effects of preoperative brachytherapy combined with radical surgery versus concurrent chemoradiotherapy (CCRT) in patients with locally advanced cervical cancer (LACC).MethodsThis retrospective study analyzed 161 patients with LACC treated at the Affiliated Hospital of North Sichuan Medical College between January 2015 and December 2020. Of these, 76 patients underwent preoperative brachytherapy combined with radical surgery (study group), while 85 received CCRT (control group). After propensity score matching (PSM) to minimize confounding, 124 patients (62 per group) were included in the analysis. Survival outcomes and prognostic factors were evaluated using Kaplan-Meier survival analysis and Cox regression models. Adverse effects of treatment were compared between the groups.ResultsAfter PSM, the 5-year progression-free survival (PFS) rate in the study group was significantly higher than that in the control group (81.2% vs. 62.7%, P<0.05). There was no significant between-group difference regarding the 5-year overall survival (OS) rate (81.4% vs. 74.9%, P=0.41). Multivariate analysis identified treatment modality (preoperative brachytherapy combined with radical surgery vs. CCRT) as an independent prognostic factor for PFS (HR: 0.458, 95% CI 0.221–0.945, P=0.035). The study group had significantly lower rates of grade 2 acute radiation enteritis, grade 3-4 leukopenia, and anemia compared to the control group (P<0.05), with no significant differences observed in other adverse effects (P>0.05).ConclusionPreoperative brachytherapy combined with radical surgery may help improve the PFS of patients with LACC, with fewer adverse effects, making it a potentially viable treatment option for these patients.